2015
DOI: 10.3389/fmicb.2015.01088
|View full text |Cite
|
Sign up to set email alerts
|

Application of modified-alginate encapsulated carbonate producing bacteria in concrete: a promising strategy for crack self-healing

Abstract: Self-healing concrete holds promising benefits to reduce the cost for concrete maintenance and repair as cracks are autonomously repaired without any human intervention. In this study, the application of a carbonate precipitating bacterium Bacillus sphaericus was explored. Regarding the harsh condition in concrete, B. sphaericus spores were first encapsulated into a modified-alginate based hydrogel (AM-H) which was proven to have a good compatibility with the bacteria and concrete regarding the influence on ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 166 publications
(88 citation statements)
references
References 44 publications
1
71
0
10
Order By: Relevance
“…Wang et al have also considered a modified‐alginate biohydrogel containing around 4 × 10 9 spores g −1 of hydrogel . Palin et al applied alginate beads to encapsulate spores of an undisclosed bacterium .…”
Section: Self‐healing Bioconcretementioning
confidence: 99%
“…Wang et al have also considered a modified‐alginate biohydrogel containing around 4 × 10 9 spores g −1 of hydrogel . Palin et al applied alginate beads to encapsulate spores of an undisclosed bacterium .…”
Section: Self‐healing Bioconcretementioning
confidence: 99%
“…This method has not been investigated for the production of microcapsules for construction and structural applications. However, recently some preliminary studies reported the use of alginate to encapsulate corrosion inhibitors [10] and bacteria for selfhealing concrete [23][24][25].…”
Section: +mentioning
confidence: 99%
“…For the same application, these alginates have also been tested with encapsulated carbonate producing bacteria [76]. To the best of our knowledge, the use of biopolymers for applications in mortar and concrete has only been reported scarcely.…”
Section: Superabsorbent Polymersmentioning
confidence: 99%